A survey of local authorities and Home Improvement Agencies: Identifying the hidden costs of providing a home adaptations service. (November 2018) - Curtis, Lesley; Beecham, Jennifer
Introduction: The Royal College of Occupational Therapists has launched a campaign to demonstrate that occupational therapists improve lives and save money for health and social care services. Occupational therapists play a major part in supporting older and disabled people to remain in their own homes through the provision of home adaptations. Among other benefits, studies have shown that home adaptations can reduce falls in the home and could therefore help reduce hospital admissions. However, to evidence savings, information on the full costs of supplying and fitting home adaptations are needed. Method: Local authorities and Home Improvement Agencies were surveyed in 2014–2015 to obtain the information required to estimate these costs. Time inputs for staff involved in their provision have been collected and staff costs and total costs calculated for 18 commonly fitted adaptations. The process of obtaining publicly funded home adaptations is also discussed. Findings: For major adaptations, the total mean cost was £16, 647, ranging from £2474 to £36, 681. Staffing costs absorbed up to 24% of the total mean cost. The total mean cost for minor adaptations was £451, with average staffing costs forming 76%. Conclusion: Staff costs are an important consideration when estimating the costs of providing home adaptations.